Short communication: Clinical evaluation of pea sprout extract in the treatment of hair loss. (3rd November 2019) - Grothe, Torsten; Wandrey, Franziska; Schuerch, Cornelia
Abstract : Hair loss affects millions of people worldwide, but currently available treatment options are often dissatisfying due to side effects or limited efficacy. Pea sprout extract has been shown to improve hair density when applied topically, but its mode of action and effectiveness upon oral administration remain unknown. Our study has now shown that the application of a fluid containing 2% pea sprout extract on a defined scalp zone of 10 volunteers enhances the expression of defined genes relevant for hair, namely fibroblast growth factor‐7 (FGF7) and noggin, by 56 and 85%, respectively. Additionally, a subsequent pilot nutrition intervention study in 21 volunteers proved that pea sprout extract is also effective when consumed as dietary supplement. The daily intake of 100 mg pea sprout extract (AnaGain™ Nu) for 8 weeks significantly reduced hair loss already after 28 days of treatment ( p  < 0.002). No adverse events were reported. Consequently, pea sprout extract may be an effective means to safely promote hair growth and reduce hair loss in individuals experiencing excessive hair shedding.